2020
DOI: 10.3390/s20010296
|View full text |Cite
|
Sign up to set email alerts
|

Towards Mixed-Initiative Human–Robot Interaction: Assessment of Discriminative Physiological and Behavioral Features for Performance Prediction

Abstract: The design of human–robot interactions is a key challenge to optimize operational performance. A promising approach is to consider mixed-initiative interactions in which the tasks and authority of each human and artificial agents are dynamically defined according to their current abilities. An important issue for the implementation of mixed-initiative systems is to monitor human performance to dynamically drive task allocation between human and artificial agents (i.e., robots). We, therefore, designed an exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…The Figure 5 shows some ET and ECG features collected during experiments. More specifically, our results, recently published in [7], indicated that the higher level of automation could be beneficial to low-scoring participants but detrimental to high-scoring ones and vice versa. In addition, inter-subject single-trial classification results showed that the studied behavioral and physiological features were relevant to predict mission performance.…”
Section: Momdp Implementations To Drive the Human-autonomous Agents Interactionsupporting
confidence: 53%
See 4 more Smart Citations
“…The Figure 5 shows some ET and ECG features collected during experiments. More specifically, our results, recently published in [7], indicated that the higher level of automation could be beneficial to low-scoring participants but detrimental to high-scoring ones and vice versa. In addition, inter-subject single-trial classification results showed that the studied behavioral and physiological features were relevant to predict mission performance.…”
Section: Momdp Implementations To Drive the Human-autonomous Agents Interactionsupporting
confidence: 53%
“…The firefighter robot game. A more recent project, based on a firefighter robotic mission [18,9,7] has been addressed in our lab in order to mitigate the drawbacks of our previous approaches: (i) the need for sufficient data to feed (MO)MDP models; (ii) the definition of a global common score reflecting mission performance, and being dependent of the efficiency of all involved agents; (iii) the implementation of a monitoring system to estimate the cognitive state of the human-operator during the interaction; and finally (iv) the evaluation in situ of the resulting (MO)MDP policy to drive such an interaction system.…”
Section: Momdp Implementations To Drive the Human-autonomous Agents Interactionmentioning
confidence: 99%
See 3 more Smart Citations